Post Mortem Examination of Barn owl in Bangladesh - A first case report - Das, BC; Das, S; Nath, BK; Parvez, MA; Hossain, S (International Journal of Natural Sciences, 2016)
The present study was the first postmortem examination of a barn owl in Bangladesh. A female Barn owl weighing 450grams was brought to the Teaching Veterinary Hospital (TVH) at Chittagong Veterinary and Animal Sciences University (CVASU) by the forest department, Chittagong. The history of traumatic injury on left wing by an electric fan one day back was recorded. Clinical and radiographic examination revealed an open overriding proximal left metacarpal fracture and was decided for pinning to correct the fracture. Retrograde intramedullary pinning was performed and immobilized the wing by bandage. At postoperative day one, owl was found death and PM was performed to find out the actual clues. Gross postmortem examination revealed chalky whitish layer formed over the heart and liver which indicates pericarditis and perihepatitis. Hemorrhage in the left thigh muscle was also observed. Biochemical examination revealed salmonella organism in the samples of liver and heart. Histopathological examination found tissue changes in the suspected organs. In conclusion, it is revealed that the probable causes of death were inanition, pain shock, unfavorable environment and with salmonella infection. International Journal of Natural Sciences (2014), 4(2) 34-37